2002
DOI: 10.1677/joe.0.1720095
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid release from rat Leydig cells: the involvement of G protein, phospholipase A2 and regulation of cAMP production

Abstract: We have previously demonstrated that the release of arachidonic acid (AA) from human chorionic gonadotropin (hCG)-stimulated Leydig cells occurs in a dose-and time-dependent manner. In addition, the amount of AA released was dependent on the hormone-receptor interaction and the concentration of LH-hCG binding sites on the cell surface. The present study was conducted to evaluate the involvement of phospholipase A 2 (PLA 2 ) and G proteins in AA release from hormonally stimulated rat Leydig cells, and the possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…It is widely accepted that the LH stimulation of Leydig cells induces the formation of the second messenger cAMP, which activates protein kinase A (PKA), and leads to the phosphorylation of several transcription factors that regulate StAR gene transcription (Reinhart et al 1999). Previous studies also indicated that LH and cAMP induce arachidonic acid (AA) release (Cooke et al 1991, Moraga et al 1997, Finkielstein et al 1998, Ronco et al 2002, Wang et al 2002. After the release of AA, its metabolic derivatives transduce signals to the nucleus to regulate StAR gene expression and steroidogenesis (Cooke 1999, Wang et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that the LH stimulation of Leydig cells induces the formation of the second messenger cAMP, which activates protein kinase A (PKA), and leads to the phosphorylation of several transcription factors that regulate StAR gene transcription (Reinhart et al 1999). Previous studies also indicated that LH and cAMP induce arachidonic acid (AA) release (Cooke et al 1991, Moraga et al 1997, Finkielstein et al 1998, Ronco et al 2002, Wang et al 2002. After the release of AA, its metabolic derivatives transduce signals to the nucleus to regulate StAR gene expression and steroidogenesis (Cooke 1999, Wang et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, arachidonic acid and/or its metabolites have been proposed to be involved in modulating the acute effects of LH on steroidogenesis (12)(13)(14)(15)(16). Arachidonic acid can be metabolized in vivo either to prostaglandins by cyclooxygenases (COX1, COX2) or into 5-hydroxyeicosatetraenoic acid and 5-hydro-peroxyeicosatetraenoic acid by 5-lipoxygenase.…”
mentioning
confidence: 99%
“…Both OTR concentrations and PKC activity were higher in the non-pregnant horns of unilaterally pregnant ewes on day 16 after oestrus than they were in the pregnant horns of the same sheep (Abayasekara et al 1995), which is consistent with oxytocin-induced production of PKC activators such as diacylglycerol or arachidonic acid. Control of arachidonic acid release from cells through endocrine or immune stimulation is consistent with paracrine or autocrine functions of fatty acids in other tissues (Zheng et al 1999, Ronco et al 2002.…”
Section: Introductionmentioning
confidence: 67%